High-risk HPV Prevalence Estimates among Older Patients: Implications for Cervical Cancer Screening Programs - Sneha Mittal; Yamini Kansal; Bhumika Singh; Vineeta Gupta (Wolters Kluwer Medknow Publications, 2024)
Background: Due to the heterogeneity of existing studies and wide range of human papilloma virus (HPV) prevalence in India, further research into the incidence of HR-HPV and its spectrum of genotypes is essential to develop screening policies. This study aimed to determine the incidence and demographic distribution of HR-HPV among cisgender female patients attending a tertiary care facility in North India. Materials and Methods: This study was conducted in the Department of Obstetrics and Gynaecology, SGRR Institute of Medical and Health Sciences, Dehradun, India. HPV-DNA test results of 653 female patients were assessed for HR-HPV positivity, genotyping, and age-based differences via Chi-square analysis. Results: Overall prevalence of HR-HPV was 4.90%, HPV-16 was 1.37%, HPV-18 was 0.76%, and HPV non-16,18 was 2.7%. In patients ≤ 50 years, prevalence of HPV-16 was 0.97%, HPV-18 was 0.38%, and HR-HPV non-16,18 was 2.71%. In patients > 50 years, prevalence of HPV-16 was 2.89%, HPV-18 was 2.17%, and HR-HPV non-16,18 was 2.89%. The difference in the prevalence of HPV-16,18 between patients ≤ and > 50 years was found to be highly statistically significant (P = 0.007485). The difference in the prevalence of total HR-HPV between patients ≤ and > 50 years was not found to be statistically significant (P = 0.059905). Conclusion: Our study's finding of higher HR-HPV positivity rates in patients > 50 years emphasizes the need for continued HR-HPV-DNA-based screening of this cohort. With widespread use in post-menopausal patients, HPV screening can serve as an important armamentarium in the fight against cervical cancer.